A radiation tolerant 12 bit, 160 MS/s data conversion and transmission ASIC for the CMS electromagnetic calorimeter. (1st April 2022) - Mazza, G.; Argirò, S.; Dellacasa, G.; Mignone, M.; Soldi, D.; Varela, J.; Wheadon, R.; ,
Abstract: The readout electronics for the CMS electromagnetic calorimeter is undergoing a re-design in order to cope with the LHC ugrade. In particular, a fourfold increase in the sampling frequency (from 40 to 160 MS/s) is required. Therefore a new readout ASIC has been developed. The ASIC, named LiTE-DTU, is designed in a CMOS 65 nm technology. The LiTE-DTU embeds two 12 bit, 160 MS/s ADCs, a time window based sample selection, lossless data compression and 1.28 Gb/s serialization. An on-chip PLL provides the 1.28 GHz clock required by the ADCs and the serializers from the 160 MHz clock.